Case report: Neonatal case of intrauterine gastrointestinal bleeding with suspected cow's milk allergy or neonatal transient eosinophilic colitis - Hoshi, Keisuke; Mukai, Takeo; Kumasawa, Keiichi; Takahashi, Naoto (Frontiers in Pediatrics, 2023)
The patient was a female newborn. Ultrasonography performed at 35 weeks and 3 days of gestation revealed honeycomb-like dilatation and peri-intestinal strong echo patterns in the gastrointestinal tract. Nonreassuring fetal status was also diagnosed, leading to an emergency Cesarean section. The baby's birth weight was 2,127 g, whereas the Apgar 1-minute and 5-minute scores were 8 and 9, respectively. The amniotic fluid showed fecal and hematogenous turbidity. After delivery, there was hematogenous intragastric residue and defecation. Thereafter, the bloody intragastric residue and fecal discharge improved. Aggregations of eosinophils in the stool were observed, and gastrointestinal allergy was suspected. Enteral feeding with the hydrolyzed protein formula was initiated and symptoms did not recur. The allergen-specific lymphocyte stimulation test was positive for lactoferrin, and the patient was suspected with neonatal cow's milk allergy or neonatal transient eosinophilic colitis. After her condition stabilized, an oral challenge test was performed using breast milk without dairy products, and the test was negative. Gastrointestinal allergy is rare even in utero, and when gastrointestinal bleeding is suspected in utero, hemorrhagic or surgical gastrointestinal diseases should be ruled out first; however, the possibility of gastrointestinal allergy should also be kept in mind.